Transformasi Perilaku Mendorong Produktivitas Organisasi - Haikal Bagas P; Ainul Yakin; Audina Aprilia; Camelia, Camelia; M. Isa Anshori (BADAN PENERBIT STIEPARI PRESS, 2023)
Companies or organizations are founded to achieve agreed targets. The process of achieving organizational goals requires many factors, including the organization's resources. Resources can be raw materials or labor within the company. A quality workforce will definitely provide maximum profits for the company. The most efficient way to increase the workforce in a company is to provide the right work motivation, combined with an appropriate leadership style and a good organizational environment. Employee commitment is also important to provide loyalty to the organization and create comfort. The aim of this research is to analyze the effect of implementing performance management on changes in employee behavior and its impact on organizational productivity. This research method uses a qualitative approach using secondary data through literature study. The research results show that motivation, transformational leadership style, and work environment have a positive impact on increasing employee performance. Employees who have high commitment will have a significant impact on the organization. Increasing the workforce also affects organizational productivity to achieve goals and obtain maximum profits.